A perspective on multinational enterprises and climate change: Learning from “an inconvenient truth”? - Kolk, Ans; Pinkse, Jonatan (Journal of International Business Studies, 2008)
This paper explores whether and how an important environmental issue such as climate change can not only give multinational enterprises the opportunity to develop “green” firm-specific advantages (FSAs), but also help reconfigure key FSAs that are viewed as the main sources of firms' profitability, growth, and survival. We examine the nature and geography of such FSA development, and develop two organizing frameworks, which are subsequently applied to climate change, using information from Global 500 firms. Implications and future directions for international business research are indicated.